CONSTRUCTION OF MDS, MDR, NEAR-MDS OR NEAR-MDR SELF-DUAL AND SELF-ORTOGONAL CODES OVER FINITE RINGS Zpm - ELVIYENTI (NIM: 20110007), MONA
In 2008, Heisook Lee and Yoojin Lee introduced a building-up method to construct self-dual or self-orthogonal codes over finite rings Zpm of even length, for pm = 25, 125, 169, 289. In this thesis we obtained new self-dual or self-orthogonal codes over finite rings Zpm of even or odd length, for pm = 25, 125, 169, 625, by combining building-up and substraction methods. We also generalized the Harada-Munemasa and Recursive method to construct other self-orthogonal codes over finite rings Zpm, for pm = 25; 125; 169. All self-dual and self-orthogonal codes are MDS, MDR, near-MDS or near-MDR.